Role of Strategic Digital Marketing Tools (Smm, Seo, and Content Marketing) in Restaurant Competitiveness and Brand Positioning (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid digitalization of the foodservice industry has transformed how restaurants communicate, compete, and position their brands in contemporary markets. With consumer decision-making increasingly shaped by online cues such as social media content, search visibility, and digital storytelling, strategic digital marketing tools have become central to restaurant competitiveness. This empirical study investigates the role of Strategic Social Media Marketing (SSMM), Search Engine Optimization Visibility (SEOV), and Content Marketing Effectiveness (CME) in shaping Brand Visibility Perception (BVP), Brand Positioning Effectiveness (BPE), and ultimately Restaurant Competitiveness Rating (RCR) among restaurants in the Indore Division of Madhya Pradesh, India. Using existing quantitative data collected from restaurant customers (N = 600), the study employs reliability analysis, factor analysis, and multiple regression techniques to examine the structural relationships among key constructs. Findings demonstrate that strategic SMM and content marketing significantly enhance brand visibility and brand positioning, while SEO-driven visibility emerges as a critical predictor of competitiveness in markets where digital search behaviour is dominant. The study highlights the importance of integrated digital marketing strategies, emphasizing that restaurants leveraging cohesive social media presence, optimized search rankings, and compelling content narratives achieve stronger market positioning and competitive advantage. Practical implications include a digital branding framework for restaurants, and theoretical implications situate digital marketing tools within contemporary branding and competitiveness models. This research contributes to 2024–25 literature by offering evidence from an emerging urban market and underscores the strategic role of digital platforms in shaping restaurant brand value and competitive success.